DAMPAK PEMBANGUNAN PLTU DI KAWASAN INDUSTRI TENAYAN RAYA KOTA PEKANBARU DAMPAK PEMBANGUNAN PLTU DI KAWASAN INDUSTRI TENAYAN RAYA KOTA PEKANBARU - Tio Anggara Putra; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
AbstractThe Environmental Impact is a focus in development to protect the environment in Pekanbaru City. The development of PLTU at Tenayan Raya Industrial Area which uses the environmental impact analysis study still raises problems. Requirements that must be completed in the preparation of the environmental impact analysis are the terms of reference, Andal and RKL-RPL. The purpose of this study was to find out and analyze related The Impact Development of PLTU at Tenayan Raya Industrial Area Pekanbaru City and analyze the factors that influence the Impact Development of PLTU at Tenayan Industrial Area in Pekanbaru City. The theory used in this study is the theory according to Jones about the stages in the policy implementation process that have indicators of the stages of interpretation, organizing stage and application stage. The research method used is a type of qualitative research with data collection techniques through interviews, observation, and documentation. The selection of research informants using purposive sampling technique. The results of this study are that the impact development of PLTU at tenayan raya industrial area in the city of Pekanbaru has not been well implemented. The influencing factors in this study are the supervision of the Environment and Hygiene Agency, the initiator's response and community participation. Keyword: The Impact of PLTU, Implementation, Tenayan Raya Industrial Area